Використання web 2.0 в менеджменті знань - Косолапов, К. С. (ХНУРЕ, 2019)
This paper describes one of the intelligent information technologies in knowledge management Web 2.0. The main source of information creation and distribution are not companies, but users. Web 2.0 has allowed move freely information over the network. Web 2.0 contributed to the creation of social networks, blogs, wikis. Free dissemination of information led to use different sources of content, which in turn allows you to look at things from different angles. This work includes advantages, disadvantages, examples of the use of this concept. This technology is intelligent because it is user-centric.